Identifying advocacy strategies, challenges and opportunities for increasing domestic health policy and health systems research funding in Nigeria: Perspectives of researchers and policymakers - Ijeoma Nkem Okedo-Alex; Ifeyinwa Chizoba Akamike; Gladys Onyinye Olisaekee; Chinyere Cecilia Okeke; Chigozie Jesse Uneke (BMC, 2021)
Abstract Introduction Poor funding for Health Policy and Systems Research (HPSR) is a major constraint to the development, generation and uptake of HPSR evidence in Low and Middle-Income countries. The study assessed the status of HPSR domestic funding and advocacy strategies for improving HPSR funding in Nigeria. It equally explored the knowledge and perception of the domestic funding status of HPSR and the effect of capacity building on the knowledge of domestic funding for HPSR in Nigeria. Methods This was a sub-national study involving policymakers and researchers from Enugu and Ebonyi States in Southeast Nigeria who participated in the sub-national Health Systems Global convening for the African region. A before-after study design (workshop) was utilized. Data collection employed semi-structured questionnaires, group and panel discussions. The workshop facilitated knowledge of HPSR, funding processes, and advocacy strategies for increased domestic funding for HPSR. Pre and immediate post-workshop knowledge assessments were done. Data were analyzed using SPSS version 25 and thematic analysis. Results Twenty-six participants were involved in the study. Half were females (50.0%) and 46.2% were aged 35-44 years. Policymakers constituted 23.1% of the participants. Domestic funding for HPSR in Nigeria was adjudged to be grossly inadequate. Identified barriers to domestic funding of HPSR included bureaucratic bottlenecks, political and policy transitions, and corruption. Potential opportunities centered on existing policy documents and emerging private sector willingness to fund health research. Multi-stakeholder advocacy coalitions, continuous advocacy and researcher skill-building on advocacy with active private sector involvement were the strategies proffered by the participants. Pre-workshop, understanding of the meaning of HPSR had the highest mean ratings while knowledge of budgeting processes and use of legal action to enable opportunities for budget advocacy for HPSR funding had the lowest mean ratings. Following the capacity-building workshop, all knowledge and understanding parameters markedly improved (percentage increase of 12.5%-71.0%). Conclusion This study found that there was paucity of domestic funding for HPSR in Nigeria alongside poor knowledge of budgeting and advocacy strategies among both policymakers and researchers. We recommend the deployment of these identified strategies and wider national and regional stakeholder engagement towards prioritizing and improving domestic funding for HPSR.